RNA-binding protein signaling in adult neurogenesis - Chan, Jackie Ngai-Man; Sánchez-Vidaña, Dalinda Isabel; Anoopkumar-Dukie, Shailendra; Li, Yue; Benson Wui-Man, Lau (Frontiers in Cell and Developmental Biology, 2022)
The process of neurogenesis in the brain, including cell proliferation, differentiation, survival, and maturation, results in the formation of new functional neurons. During embryonic development, neurogenesis is crucial to produce neurons to establish the nervous system, but the process persists in certain brain regions during adulthood. In adult neurogenesis, the production of new neurons in the hippocampus is accomplished via the division of neural stem cells. Neurogenesis is regulated by multiple factors, including gene expression at a temporal scale and post-transcriptional modifications. RNA-binding Proteins (RBPs) are known as proteins that bind to either double- or single-stranded RNA in cells and form ribonucleoprotein complexes. The involvement of RBPs in neurogenesis is crucial for modulating gene expression changes and posttranscriptional processes. Since neurogenesis affects learning and memory, RBPs are closely associated with cognitive functions and emotions. However, the pathways of each RBP in adult neurogenesis remain elusive and not clear. In this review, we specifically summarize the involvement of several RBPs in adult neurogenesis, including CPEB3, FXR2, FMRP, HuR, HuD, Lin28, Msi1, Sam68, Stau1, Smaug2, and SOX2. To understand the role of these RBPs in neurogenesis, including cell proliferation, differentiation, survival, and maturation as well as posttranscriptional gene expression, we discussed the protein family, structure, expression, functional domain, and region of action. Therefore, this narrative review aims to provide a comprehensive overview of the RBPs, their function, and their role in the process of adult neurogenesis as well as to identify possible research directions on RBPs and neurogenesis.